2006
DOI: 10.2460/javma.229.7.1134
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal pasture myopathy in horses in the midwestern United States: 14 cases (1998–2005)

Abstract: Cases of rhabdomyolysis have been attributed to white snakeroot toxicosis; however, tremetone was not detected in any horses. Similarities exist between cases of seasonal pasture myopathy and cases of atypical myopathy in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 16 publications
5
76
0
2
Order By: Relevance
“…In 2006, a similar condition called seasonal pasture myopathy was recognised in the USA (Finno and others 2006); cases also exhibited a MADD-like biochemical profile (Sponseller and others 2012). Following a botanical survey, it was hypothesised that the condition was caused by ingestion of seeds from Acer negundo (box elder tree) (Fig 5) as these trees were present on all pastures associated with cases.…”
Section: History Of Atypical Myopathy In Europementioning
confidence: 99%
“…In 2006, a similar condition called seasonal pasture myopathy was recognised in the USA (Finno and others 2006); cases also exhibited a MADD-like biochemical profile (Sponseller and others 2012). Following a botanical survey, it was hypothesised that the condition was caused by ingestion of seeds from Acer negundo (box elder tree) (Fig 5) as these trees were present on all pastures associated with cases.…”
Section: History Of Atypical Myopathy In Europementioning
confidence: 99%
“…Cases have also been identified in New Zealand (McKenzie et al 2013) and Australia (Irwin and Pulsford 1951). In the United States, a similar condition has been called seasonal pasture myopathy (SPM; Finno et al 2006).…”
Section: Identifying the Cause: Historymentioning
confidence: 99%
“…Also, outbreaks of acute nonexertional pasture-associated rhabdomyolysis that strongly resemble AM were described in Canada [6] and in the United States of America (USA) [7, 22]; the USA syndrome was called seasonal pasture myopathy (SPM). It is now believed that SPM is indeed similar to AM as it has been showed that biochemical defects of both syndromes are identical [23, 24].…”
Section: From the Beginningmentioning
confidence: 99%
“…However, it is difficult from the literature to point out a specific climatic feature. The weather prior to the onset of outbreaks was described as ‘‘very wet and cold” [9, 12], ‘‘stormy, cold, and humid” [10], ‘‘stormy” [8], or ‘‘stormy and humid” [3, 13, 22, 31]. Moreover, Belgian outbreaks were characterized by a lack of solar radiation, an excess of precipitation or relative humidity, and no frost in the preceding days [3].…”
Section: Historymentioning
confidence: 99%